1979
DOI: 10.1111/j.1365-2133.1979.tb08080.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous resolution of lichen myxoedematosus

Abstract: Lichen myxoedematosus was diagnosed in a 44-year-old woman in 1957. Despite the persistence of an abnormal serum protein, the skin lesions cleared by 1965. The protein abnormality disappeared several years later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0
2

Year Published

1986
1986
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 10 publications
0
21
0
2
Order By: Relevance
“…14 Although lichen myxedematosus usually runs a protracted, unremitting course, exceptional cases of spontaneous resolution have been reported. [15][16][17] Interestingly, the 29-year-old patient described by Kwon et al 17 presented with lichenoid skin lesion on the back of his hands, extensor surfaces, and periorbital region, common sites of involvement in SHJCM. Stephens et al 18 also reported spontaneous resolution of papular mucinosis in a patient with associated carpal tunnel syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…14 Although lichen myxedematosus usually runs a protracted, unremitting course, exceptional cases of spontaneous resolution have been reported. [15][16][17] Interestingly, the 29-year-old patient described by Kwon et al 17 presented with lichenoid skin lesion on the back of his hands, extensor surfaces, and periorbital region, common sites of involvement in SHJCM. Stephens et al 18 also reported spontaneous resolution of papular mucinosis in a patient with associated carpal tunnel syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The encouraging results obtained in our three cases mimic the good results obtained previously in other rheumatic diseases such as dermatomyositis, Still's disease, systemic lupus erythematosus, and vasculitides. [6][7][8][9][10] In autoimmune diseases, IVIg treatment may have additional effects, such as the modulation of immunological reactivity and of inflammatory reactions with different mechanisms of action. However, it is difficult to speculate on the mechanism that led to the improvement of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-idiotypic antibodies may bind and down regulate the B cell receptor for antigen, may eventually bind to T cells regulating their function, and may have an immunomodulatory action by FcR blockade. 6 Cytokines derived from macrophages or activated T cells can exert a direct cytotoxic effect on many tissues. IVIg contains specific high affinity antibodies against interleukins (IL1α and IL6) and tumour necrosis factor α (TNFα), thus suppressing the continuing immune response in different disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A case of lichen myxedematosus [2] regressed 11 years after its onset. Again, lesions were multiple and parapro teinemia was present.…”
Section: Discussionmentioning
confidence: 99%